Solar PV fed non-isolated DC-DC converter for BLDC motor drive with speed control - G. G RajaSekhar; Basavaraja Banakar (Institute of Advanced Engineering and Science, 2019)
Brushless DC motors (BLDC) are predominantly used these days due to its meritorious advantages over conventional motors. The paper presents PV fed BLDC speeds control system. A closed-loop interleaved boost converter increases the voltage from PV system to required level. Converter for BLDC operates at fundamental switching frequency which reduces losses due to high switching frequency. Internal current control method is developed and employed for the speed control of PV fed BLDC motor by sensing the actual speed feedback. Internal current controlled PV fed BLDC drive is analyzed with increamental speed with fixed torque and decreamental speed with fixed torque operating conditions. Also the system with speed control is verified for variable torque condition. The system is developed and results are developed using MATLAB/SIMULINK software.